Effect of PbS on ZnS nanostructure deposited using thermal evaporation: growth, morphological and structural study - B Muhammad Abdalla; M Kakhia; A M Obied; W A Zetoune (Iranian Journal of Physics Research, 2021)
ZnS film has been deposited on PbS buffer layer using thermal evaporation, the ZnS film has nanostructure (nanowires) due to effect of PbS which play role of catalyst. This growth for non doped films have dense structure (for PbS and ZnS films). SEM morphology of ZnS/PbS, ZnS and PbS have been studied in details (surface and cross section). Atomic force microscopy (AFM) used to characterized the thins films (ZnS and PbS). X-ray photoelectron spectroscopy (XPS) and EDX techniques have utilized to know the chemical and stoichiometry of deposited films. The crystallographic properties have been studied using XRD patterns, it found that the results in Raman and XRD characterization have a good agreement. UV-Vis spectroscopy is used to acquire an idea about optical properties of thin films deposited on glass substrate. The deposited ZnS nanowires and thin film have hexagonal phase, which indicate to the buffer layer, which does not affects the structural but changes the growth mechanism. High Resolution Transmission Electron Microscope (HRTEM) images have confirmed the formation of ZnS nanowires.